(untitled) (Faridpur Medical College Journal, 2016)
Lichen planus (LP) is a common inflammatory disorder that affects the skin, mucous membranes, nails and hair. There are various modalities of treatment but none is curative. Betamethasone oral mini-pulse (OMP) therapy has been used effectively and safely in vitiligo, alopecia areata and lichen planus. We sought to evaluate the efficacy and safety of Betamethasone OMP in patients with lichen planus. This prospective study was carried out among patients with lichen planus fulfilling the inclusion criteria, attending the skin and VD outpatient department of Dhaka Medical College Hospital, Dhaka Bangladesh over a period of 6 months from January 2005 to June 2005. A total of 20 patients with lichen planus diagnosed clinically and confirmed by histopathological examination were selected randomly for this study. Among them both male and female were in equal number. The study subjects were treated with 5 mg of Betamethasone orally on 2 consecutive days per week, for 3 months. Treatment response and side effects were monitored 4 weekly. The response was good in 60% and fair in 40% and there was no excellent response. This study indicates that further prospective placebo controlled studies are needed to clarify the efficacy of oral Betamethasone in lichen planus. Faridpur Med. Coll. J. Jul 2015;10(2): 47-49